BUDIDAYA IKAN DALAM EMBER (BUDIKDAMBER) SEBAGAI SOLUSI KETAHANAN PANGAN KELUARGA PADA LAHAN SEMPIT DI DESA SANTONG, KABUPATEN LOMBOK UTARA - Bagus Dwi Hari Setyono; Rangga Idris Affandi; Yuliana Asri (Universitas Mataram, 2022)
The Covid-19 pandemic that occurred in Indonesia in 2020 has an impact on the community's economy, including the people of Santong Village, Kayangan, North Lombok. Economic recovery is carried out starting from meeting daily food needs with one of its activities, namely the aquaculture in buckets (budikdamber). Budikdamber is a solution for aquaculture in narrow areas with efficient use of water, easy for people to do at home with small modes and finally able to meet nutritional needs. The purpose of this community service activity is to promote, develop, and assist fish farming activities using the Budikdamber system (aquaculture in buckets) to residents of Santong Village, Kayangan, North Lombok. The use of this community service is carried out by lecture and mentoring methods, namely introducing and direct practice of budikdamber activities. This service activity was started by making a presentation introducing budikdamber (aquaculture in buckets), discussion, and direct practice to the community of Santong Village. The result of this community service activity was that the first counseling was carried out with the material presented related to budikdamber which was followed by the PKK group, the aquaculture group, and several students who were carrying out KKN activities. After that, direct practice of making budikdamber begins with the preparation of tools and materials. If the tools and materials are ready, then proceed with the activities of making budikdamber. Next is the maintenance of budikdamber which will eventually be harvested. Fish that can be used are catfish, carp, tilapia, sepat, while vegetables that can be grown are spinach, lettuce, kale, pakcoy, and mustard greens. The conclusion of this community service is that information, knowledge, and technical guidance have been conveyed to the community in Santong Village about budikdamber technology.